Consumer Perceptions that Influence Choice of Pharmacy Hashifah 02 Makassar City as A Place for Self-Medication - Rina Asrina; Gerfan Patandung; Wirasti Evivania (Jurnal Farmasi Sandi Karsa, 2022)
Health facilities in the form of pharmacies are very easy to find anywhere and are affordable by the community so that consumers can freely choose a pharmacy that suits their wishes which can be influenced by several things. This study aims to determine consumer perceptions that influence the selection of Apotek Hashifah 02 Makassar City as a place for self-medication. This research was conducted using a descriptive survey method using a questionnaire as a data collection tool. This research was conducted in March 2022 by distributing questionnaires to 97 people who came to the Hashifah 02 Pharmacy Makassar City and according to the respondents' criteria. The results showed that the reasons for consumers to self-medicate at Hashifah Pharmacy 02 were close distance (75%), fast service (100%), friendliness of officers in drug services (100%), staff's ability to provide drug information (100%). , cheap drug prices (91%), complete medicines (90%), strategic location of pharmacies (90%) clean pharmacy conditions (100%), spacious and comfortable waiting room (69%), recommendations from acquaintances or family (43%), employees who look neat and polite (100%). So it can be concluded that consumer perceptions that affect the selection of Hashifah 02 Pharmacy Makassar City as a place for self-medication are fast service, friendliness of officers in drug services, the ability of officers to provide drug information, clean pharmacy conditions, and employees who look neat and polite.